Media Pembelajaran Berbasis Smarthphone dalam Upaya Meningkatkan Motivasi Belajar - Yanti Arasi Sidabutar; Dyan Wulan Sari HS; Marlina Angkis Tambunan; Natalina Purba; Lisbet Novianti Sihombing (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
The purpose of this study was to determine the use of smartphone-based learning media on student learning motivation. The type of research method used in this research is a quasi-experimental method or Quasi-Experiment to see student motivation. The sampling technique used in this study was 25 people in the PGA6 group in the UHKBNP PGSD Study Program. Data collection techniques in this study used a learning motivation questionnaire and essay tests. Based on the results of the study, namely the learning outcomes before using TikTok media 71.04 and after using TikTok media 82.24. Based on the results of the analysis of student learning motivation, it is known that student learning motivation using TikTok media is 84.8 and without using TikTok media is 78.5. Thus, smartphone-based learning media can increase the learning motivation of UHKBNP PGSD students.